Heart remodeling in elderly patients with isolated systolic arterial hypertension and chronic heart failure with preserved left ventricular ejection fraction - S. O. Sheiko; N. O. Kolb (Zaporožskij Medicinskij Žurnal)
The aim of the work was to study the structural and functional state of the left ventricle (LV) in elderly patients with isolated systolic arterial hypertension (ISAH) and chronic heart failure with preserved ejection fraction (CHF with PEF).